The Influence of Financial Literacy and Religiosity on Students’ Investment Decisions: A Comparative Study between Boarding School and Non-Boarding School Students - Indah Warih Yanti; Muhammad Sabandi (Universitas Negeri Semarang, 2025)
This study aims to analyze the influence of financial literacy and religiosity on investment decisions, and to compare the differences in these influences on Islamic boarding school students and non-Islamic boarding school students in Surakarta City. This study is a quantitative study with a sample of 165 university students in Surakarta City, both with and without an Islamic boarding school background. Data collection techniques used tests and questionnaires in the form of Google Forms. Data analysis techniques used descriptive analysis, normality tests, linearity tests, multicollinearity tests, heteroscedasticity tests, and multiple linear analysis. The results of this study indicate that 1) financial literacy has a positive and significant effect on investment decisions, obtaining a regression coefficient of 0.574 and a calculated t of 2.286. The calculated t value > t table (2.286 > 1.974) and a significance value of 0.024 is smaller than 0.05 (0.024 < 0.05); 2) religiosity has a positive and significant effect on investment decisions, obtaining a regression coefficient of 0.271 and a calculated t of 4.221. The calculated t value > t table (4.221 > 1.974) and the significance value of 0.000 is smaller than 0.05 (0.024 < 0.05). 3) Islamic boarding school students have a greater influence on investment decisions than non-Islamic boarding school students, obtaining a determination coefficient (R²) of 0.505 and non-Islamic boarding school students of 0.396.